The dynamics of apoplast phenolics in tobacco leaves following inoculation with bacteria - Baker, Con J.; Mock, Norton M.; Smith, Jodi M.; Aver'Yanov, Andrey A. (Frontiers in Plant Science, 2015)
This study demonstrates that the accumulation of apoplastic phenolics is stimulated in planta in response to bacterial inoculation. Past studies have shown that levels of extracellular phenolics are elicited in plant cell suspensions in response to bacteria, and that tomato plants infected with viroids showed changes in apoplastic phenolics. The method described here monitored changes in apoplastic phenolics in tobacco leaves following bacterial inoculation of the same tissue. Inoculation with a saprophyte, Pseudomonas fluorescens, which does not cause visible symptoms or physical damage, was used to elicit phenolics and examine the effects of variable parameters on phenolic composition. Location of the inoculation on the leaf, position or developmental age of the leaf on the plant, and inoculum concentration were standardized for further experiments. The patterns of phenolic change in the apoplast were compared for tobacco inoculated with P. syringae pathovars, pv. syringae, which causes a resistant HR reaction within 15 h, and pv. tabaci, which causes a susceptible reaction with delayed visible symptoms. Both pathogens elicited lower increased levels of acetosyringone compared to the saprophyte, P. fluorescens but had greatly increased levels of the chlorogenic acid derivatives. The latter metabolites appear to have come from the intracellular stores, which could